Tarekat Shiddiqiyah dalam Masyarakat Jawa Pedesaan - Sehat Ihsan Shadiqin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
This article discusses the development and the influence of tarekat in  societal life of rural Javaness. Some researchers on modern tarekat in Indonesia,  like Bruinessen and Howel, argued that practicing tarekat now shifts from rural to  urban community, which is known as urban Sufism. The unique relation between  sheikh and student gradually being left by the urban Sufism and being changed by  ability in rhetoric and connecting religious teaching to modern life issues by using  spiritual approaches. Based on my field experience, this argument is not totally  relevant and true, especially in rural community of Javaness. Tarekat is not  influenced by the development of modern communication and telecommunication.  Tarekat remains as inseparable part of rural religious social life. This research was  conducted in January 2012 in a remote village of Pekalongan, Central Java.  While I took part in various activities of the Tarekat Shiddiqiah members, I  interviewed some of the members. By doing this, I sum up that the development  of modern communication and transportation does not necessarily change the map  of tarekat in rural community. The attachment of Javaness mystical tradition to  tarekat helps the tarekat develop within community.